Clinical Evaluation of Standardized Fronto-Orbital Advancement for Correction of Isolated Trigonocephaly. Issue 1 (January 2018) - Safi, Ali-Farid; Kreppel, Matthias; Grandoch, Andrea; Kauke, Martin; Nickenig, Hans-Joachim; Zöller, Joachim
Abstract : Abstract: Corrective surgery of trigonocephaly is a major challenge, owing to the complex development of the craniofacial skull. Although reports on the clinical success of standardized fronto-orbital advancement have been promising, there is a lack of studies, assessing this method. Hence, the aim of our study was to evaluate the clinical outcome of a standardized fronto-orbital advancement procedure for correction of isolated nonsyndromic trigonocephaly, in our patient cohort. The retrospective study included 30 patients from 2008 to 2015. Inclusion criteria were treatment-naive children with isolated nonsyndromic trigonocephaly, being treated with standardized frontoorbital advancement in our department. We considered postoperative complications and the Whitaker Score to evaluate the success of the clinical outcome. Surgery was performed at a mean age of 9.3 months. The mean operation time was 153 minutes. All patients were assigned I according to the Whitaker score. One patient suffered from a small inconsequential subdural hematoma. Another patient suffered from dural tears, which were identified and treated intraoperatively. No major complications occurred within our patient cohort. The standardized fronto-orbital advancement is a safe and successful method, as it is associated with a high morphological outcome and low complication rate.